A Comparative Effectiveness Study of a Shortened Trauma Recovery Empowerment Model and an Attachment-Informed Adaptation. (April 2020) - Masin-Moyer, Melanie; Engstrom, Malitta; Solomon, Phyllis
Relational challenges often associated with interpersonal trauma may hinder survivors' abilities to fully benefit from group therapy. This quasi-experimental study compared clinical outcomes of a 16-week version of the Trauma Recovery and Empowerment Model (TREM) for women and an attachment-informed adaptation (ATREM). Prior findings of TREM are extended by demonstrating that both group conditions can facilitate comparable clinical outcomes, creating options for group facilitators. Only ATREM resulted in statistically significant improvement in individual attachment avoidance, and it trended toward a slightly higher completion rate. This study provides insight into the emerging concept of group attachment.